Mechanical Properties of Rice Husk Filled Impact Modified PVC-U Composite - Ahmad, Mazatusziha (2004)

(untitled)
The growing interest in environmentally friendly materials has produced reevaluation of organic materials as fillers in plastics. Composite materials made from plant fibre are receiving a great deal of attention today since they are biodegradability, very low cost, recyclability, and renewable nature. Rice husk (RH) is one of the natural fillers that offer a number of advantages over inorganic fillers. This study investigates the performance of RH as filler for unplasticised polyvinyl chloride (PVC-U) composites. Acrylic impact modifier at 4,8,10 and 12 phr were used to enhance the impact properties of PVC. The composites with RH loadings varied from 10 to 40phr were prepared using two roll mill at temperature 165oC for 10 minutes of milling time. The composites milled sheets were then placed into a mould and hot pressed at temperature 185oC and pressure of 120kg/m2 for 5 minutes. The cooling time used was 5 minutes before the specimens being removed from the mould.